Pendekatan Human Relations Dalam Membangun Budaya Mutu Dan Kinerja Organisasi Pendidikan - Rosmiati Ramli; Mardiati M; Nursia Nursia; Zulbina Zulbina; Misbah Misbah; Juhariati Juhariati (Jurnal Ilmiah Multidisiplin Mahasiswa dan Akademisi, 2026)
The increasing complexity of the educational sector requires educational institutions to focus not only on technical management aspects but also on the development of interpersonal relationships within organizations. The Human Relations approach emphasizes the importance of effective communication, collaboration, motivation, and job satisfaction in enhancing organizational effectiveness. This article aims to examine the role of the Human Relations approach in fostering a quality culture and improving educational organizational performance. The study employed a library research method by analyzing relevant books, scientific journals, conference proceedings, and research reports. Data were analyzed using content analysis through identification, classification, interpretation, and synthesis of information. The findings indicate that the Human Relations approach contributes to the development of a quality culture through five key dimensions: organizational communication enhancement, work motivation strengthening, participative leadership development, teamwork improvement, and the creation of a conducive organizational climate. These dimensions promote organizational member engagement, strengthen commitment to quality, and support sustainable educational management effectiveness. Theoretically, this study reinforces the understanding that social and psychological factors are strategic elements in establishing a quality culture in education. Practically, the findings provide guidance for school principals, teachers, and educational managers in creating productive work environments oriented toward continuous improvement. The novelty of this article lies in its comprehensive synthesis that integrates Human Relations, quality culture, and educational organizational performance into a unified conceptual framework.